Dynamic interference in the photoionization of He by coherent intense high-frequency laser pulses: direct propagation of the two-electron wave packets on large spatial grids - Artemyev, Anton; Müller, Anne D.; Hochstuhl, David; Cederbaum, Lorenz S.; Demekhin, Philipp V. (Physical review, 2016)
The direct ionization of the helium atom by intense coherent high-frequency short laser pulses is investigated theoretically from first principles. To this end, we solve numerically the time-dependent Schrödinger equation for the two-electron wave packet and its interaction with the linearly polarized pulse by the efficient time-dependent restricted-active-space configuration-interaction method (TD-RASCI). In particular, we consider photon energies which are nearly resonant for the 1s→2p excitation in the He+ ion. Thereby, we investigate the dynamic interference of the photoelectrons of the same kinetic energy emitted at different times along the pulse in the two-electron system. In order to enable observation of the dynamic interference in the computed spectrum, the electron wave packets were propagated on large spatial grids over long times. The computed photoionization spectra of He exhibit pronounced interference patterns the complexity of which increases with the decrease of the photon energy detuning and with the increase of the pulse intensity. Our numerical results pave the way for experimental verification of the dynamic interference effect at presently available high-frequency laser pulse sources.
Gesehen am 18.08.2020